Ніжинське студентство кінця ХІХ – початку ХХ ст.: перспективи дослідження - Гайденко, О.В. (Сіверщина в історії України, 2021)
Стаття присвячена перспективам подальшого дослідження студентства Ніжинського історико-філологічного інституту князя Безбородька у період кінця ХІХ – початку ХХ ст. Ніжинське студентство розглядається крізь призму загальноімперського, саме тому дається огляд основних здобутків радянської та пострадянської історіографії зі студентського питання та еволюції його висвітлення. Наголошується на тому, що до цього часу немає праці, у якій увага приділялася б саме студентам інституту Безбородька, їхньому повсякденному життю, а не викладачам, внутрішньому розпорядку закладу чи суспільно-політичним метаморфозам. Визначені шляхи подальшої дослідницької роботи: соціальний та ідеальний образи студентства, його побутове життя, специфіка навчання в історико-філологічному інституті. Дана робота має стати першою у написанні всебічної наукової праці з окресленої тематики. The article is devoted to the prospects of further research of the students of the Nizhyn Historical and Philological Institute of Prince Bezborodko in the period of the end of the 19th – the beginning of the 20th century. Nizhyn students are considered through the prism of the general imperial, which is why an overview of the main achievements of Soviet and post-Soviet historiography on the student issue and the evolution of its coverage. It is emphasized that so far there is no work in which attention is paid to the students of the Bezborodko Institute, their daily lives, but not to teachers, the internal regulations of the institution or socio-political metamorphoses. The uniqueness of the Nizhyn Institute of History and Philology is that there were no such pedagogical institutions in the Russian Empire, except for the Imperial St. Petersburg Institute of History and Philology. Researchers often overlooked institutes and schools that produced a significant number of specialists in various fields. All these educational institutions formed their own intelligentsia, with all its peculiarities (political and artistic preferences, general worldview, etc.). Little attention is paid to the provincial students of the Russian Empire. By analyzing archival sources it will be possible to answer the following questions: how the rhythm of life of the school was built, the main aspect was the education or upbringing of future teachers and officials, what was the specifics of studying at the Nizhyn Institute, and try to create social and ideal images students, their domestic life (hobbies, food, clothes, love and sex, part-time work, etc.). Need to deepen the research of students’ military service and postscripts most of them to the conscription districts.